2021
DOI: 10.1016/j.isci.2021.103533
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral VEGF-B186R127S gene transfer induces angiogenesis and improves perfusion in ischemic heart

Abstract: Summary Vascular endothelial growth factor B (VEGF-B) is an interesting therapeutic candidate for coronary artery disease. However, it can also cause ventricular arrhythmias, potentially preventing its use in clinics. We cloned VEGF-B isoforms with different receptor binding profiles to clarify the roles of VEGFR-1 and Nrp-1 in angiogenesis and to see if angiogenic properties can be maintained while avoiding side effects. VEGF-B constructs were studied in vivo using adenovirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…To avoid this problem, we recently designed different isoforms of VEGF-B186, as it was unclear whether the angiogenic potential or arrhythmogenic stimuli of VEGF-B186 is due to the full-length VEGF-B186 or whether NRP1 binding after the proteolytic processing contributes to these effects. We demonstrated that full-length VEGF-B186 is solely responsible for angiogenesis, and no arrhythmogenic stimuli were observed with the full length or the NRP1 binding isoforms in this study ( Korpela et al, 2021 ).…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…To avoid this problem, we recently designed different isoforms of VEGF-B186, as it was unclear whether the angiogenic potential or arrhythmogenic stimuli of VEGF-B186 is due to the full-length VEGF-B186 or whether NRP1 binding after the proteolytic processing contributes to these effects. We demonstrated that full-length VEGF-B186 is solely responsible for angiogenesis, and no arrhythmogenic stimuli were observed with the full length or the NRP1 binding isoforms in this study ( Korpela et al, 2021 ).…”
Section: Introductionmentioning
confidence: 57%
“…Human serotype 5 adenoviral vectors were produced by National Virus Vector Laboratory at Biocenter Kuopio, Finland ( Korpela et al, 2021 ). Adenoviral vector titers were spectrophotometrically determined at OD260 nm ( Sweeney and Hennessey, 2002 ).…”
Section: Methodsmentioning
confidence: 99%
“…VEGF-B mainly binds to VEGFR-1 and NRP-1, and plays an important role in tumor angiogenesis and in the improvement of ischemic conditions [29,30]. VEGF-C and VEGF-D mainly bind to VEGFR-3 and participate in lymphangiogenesis [30,31].…”
Section: Angiogenic Function: Tumor Vasculaturementioning
confidence: 99%
“…In connection with coronary vessels, VEGF-B promotes angiogenesis in the subendocardial region and rescues the myocardium after myocardial infarction [ 52 ]. Our studies have shown that adenoviral vector-based VEGF-B186 gene transfer induced significant angiogenesis in the myocardium and improved myocardial perfusion without increasing a coronary steal effect [ 28 , 43 , 45 , 55 ]. Thus, VEGF-B186 seems highly beneficial for the treatment of CHD [ 43 , 45 ].…”
Section: Cardioprotective Role Of Vegf-bmentioning
confidence: 99%
“…Our studies have shown that adenoviral vector-based VEGF-B186 gene transfer induced significant angiogenesis in the myocardium and improved myocardial perfusion without increasing a coronary steal effect [ 28 , 43 , 45 , 55 ]. Thus, VEGF-B186 seems highly beneficial for the treatment of CHD [ 43 , 45 ]. However, it has remained unclear if both unprocessed and proteolytically processed forms or specific forms of VEGF-B186 contribute to the neovascularization process.…”
Section: Cardioprotective Role Of Vegf-bmentioning
confidence: 99%